Treatment outcome and long-term stability of skeletal changes following maxillary distraction in adult subjects of cleft lip and palate - Satinder Pal Singh; Ashok Kumar Jena; Vidya Rattan; Ashok Kumar Utreja (Wolters Kluwer Medknow Publications, 2012)
Aim : To evaluate the treatment outcome and long-term stability of skeletal changes following maxillary advancement with distraction osteogenesis in adult subjects of cleft lip and palate. Materials and Methods: Total 12 North Indian adult patients in the age range of 17-34 years with cleft lip and palate underwent advancement of maxilla by distraction osteogenesis. Lateral cephalograms recorded prior to distraction, at the end of distraction, 6 months after distraction, and at least 24 months (mean 25.5 ± 1.94 months) after distraction osteogenesis were used for the evaluation of treatment outcome and long-term stability of the skeletal changes. Descriptive analysis, ANOVA, and post-hoc test were used, and P-value 0.05 was considered as a statistically significant level. Results: Maxillary distraction resulted in significant advancement of maxilla (P<0.001). Counterclockwise rotation of the palatal plane took place after maxillary distraction. The position of the mandible and facial heights were stable during distraction. During the first 6 months of the post-distraction period, the maxilla showed relapse of approximately 30%. However, after 6 months post distraction, the relapse was very negligible. Conclusions: Successful advancement of maxilla was achieved by distraction osteogenesis in adult subjects with cleft lip and palate. Most of the relapse occurred during the first 6 months of post-distraction period, and after that the outcomes were stable.